Combining ability for yield and quality in Sugarcane - S.Alarmelu, G.Hemaprabha, R.Nagarajan and R. M..Shanthi (Electronic Journal of Plant Breeding, 2010)
Combining ability variances and effects were estimated for important yield and quality traits in sugarcane using line xtester mating design.Seven clones were used as females (lines) and three as males (testers). Five characters viz., numberof millable canes, stalk diameter, stalk height, single cane weight and Brix % were considered in the present study.Twenty one crosses, obtained from seven lines x three testers were studied for sca, gca effects, per-se performance andheterosis. The study revealed no association between combining ability effect and heterotic response. Among the lines,Co 740, Co 86032 and Co 98010 and among the testers, Co 99006 was found to be good general combiner for agronomiccharacters. Four crosses viz., Co 86002 x Co 94008, Co 86032 x Co 99006, Co 98010 x Co 775 and Co 93020 x Co99006 were promising for all the traits. Estimates of variance due to gca and sca and their ratio revealed predominantlynon-additive gene action for these characters. Since sugarcane is a vegetatively propagated crop, heterosis can be fixedand exploited in F1 generation. The crosses viz., Co 740 x Co 99006, Co 93020 x Co 94008, Co 8371 x Co 775, Co 86002x Co 94008, Co 86032 x Co 99006 and Co 98010 x Co 99006 showed significant heterotic response for the traits understudy. The present study rendered identification of new lines, testers and crosses for development of new varieties withimproved yield and quality traits